Quantification analysis of lactate dehydrogenase and C-reactive protein in evaluation of the severity and prognosis of the acute pancreatitis - Yin, Xiang; Xu, Jing; Zhang, Qi; Yang, Li; Duan, Yunjie (Cellular and Molecular Biology, 2020)
To evaluate the value of C-reactive protein (CRP) and lactate dehydrogenase (LDH) in assessing the severity and prognosis of acute pancreatitis (AP). A retrospective analysis was performed with the clinical data of 115 AP patients who were delivered to this hospital between December 2012 and December 2017 for treatment, in which there were 76 patients with mild AP (MAP group) and 39 with moderately severe AP (MSAP) and severe AP (SAP) (non-MAP group). Within 24 h after admission, we detected the levels of CRP, LDH and amylase (AMY) in serum, and according to the sensitivity and specificity of CRP, LDH and AMY, as well as the SROC curve, we evaluated the diagnostic value of these indicators in assessing the severity of AP. In serum, the levels of CRP and LDH in the non-MAP group were significantly higher than those in the MAP group (P <0.05). And in predicting the development of AP, the sensitivity, specificity and accordance rate of CRP were 59.0%, 97.4% and 84.3%, with a cut-off value of 176.00 mg/L; for LDH, these indexes were 94.9%, 88.2% and 90.4%, with a cut-off value of 235.50 U/L. Thus, LDH, combined with the CRP can well predict the incidence rate of the MODS and mortality rate of AP. Finally, we conclude that within 24 h after admission, the levels of CRP and LDH in patients can serve as indicators for evaluating the severity and prognosis of AP.